Microwave-Assisted Transfer Hydrogenation of Carbonyl and Nitro Compounds Using Bimetallic Ru(II) Cymene Complexes - Deshmukh, Gopal; Murugavel, Ramaswamy (Synlett, 2024)
We report an investigation of the microwave-assisted catalytic transfer hydrogenation (TH) of carbonyl and nitro compounds by employing Ru(II) complexes: bimetallic [(p-cymene)2(RuCl)2L1]2X (X = BF4 (Cat2); X = PF6 (Cat3)) and mononuclear [(p-cymene)(RuCl)L2]BF4 (Cat4) (where L1 = N,N′-(3,3′,5,5′-tetraisopropyl-[1,1′-biphenyl]-4,4′-diyl)bis(1-(pyridin-2-yl)methanimine) and L2 = N-(2,6-diisopropylphenyl)-1-(pyridin-2-yl)methanimine). At a low catalyst loading of 0.01 mol% (Cat2/Cat3), a broad range of substrates, comprising aromatic as well as aliphatic ketones and aldehydes, undergo the TH reaction in a short reaction time of just 10 minutes. Additionally, chemoselective hydrogenation of nitroaromatic compounds is achieved under microwave irradiation in the presence of Cat2 within 5 minutes. Control experiments demonstrate that microwave heating conditions outperform conventional heating in terms of improved catalytic activity and reaction efficiency. The bimetallic catalyst Cat2 is used at a very low loading of 0.001 mol% to achieve high TONs and TOFs of 7.7 × 104 and 2.3 × 105 h–1, respectively, for the TH reaction. Spectrometry experiments involving trapping of intermediates are used to propose a mechanism for the TH of the carbonyl compounds.
Keywords: bimetallic; microwave; transfer hydrogenation; ruthenium; mechanism